Directions in ESP Research: Implications in Malaysia - Omar, Asmah Haji (Journal of Modern Languages, 2017)
This study considers features of ESP used in the English language in general as well as the features that are idiosyncratic to Malaysia. The study suggests a categorisation of ESP into upper and lower nodes above which is the supraregister of ESP. Such a categorisation serves as a useful guide in the selection of areas or domains and subdomains to work on. The establishment of domains and subdomains should be used in needs analysis.